Lymph node trafficking and antigen presentation by endobronchial eosinophils - Shi, Huan-Zhong (American Society for Clinical Investigation, 2000)
Because eosinophils recruited into the airways in allergic diseases are exposed to inhaled allergens, we evaluated whether eosinophils within the endobronchial lumen can function in vivo as antigen-presenting cells for inhaled antigens. We recovered eosinophils from the airways after aerosol antigen challenge in sensitized mice or from the peritoneal cavities of IL-5 transgenic mice and fluorescently labeled these cells ex vivo. These labeled cells, instilled intratracheally into normal mice, migrated into draining paratracheal lymph nodes and localized to T cell–rich paracortical areas. The homing of airway eosinophils to lymph nodes was not governed by eotaxin, because CCR3(–/–) and CCR3(+/+) eosinophils migrated identically. Airway eosinophils, recovered after inhalational antigen challenge in sensitized mice, expressed MHC class II and costimulatory CD80 and CD86 proteins and functioned in vitro as CD80- and CD86-dependent, antigen-specific, antigen-presenting cells. Moreover, when instilled into the airways of antigen-sensitized recipient mice, airway eosinophils recovered after inhalational antigen challenge stimulated antigen-specific CD4(+) T cell proliferation within paratracheal lymph nodes. Thus, eosinophils within the lumina of airways can process inhaled antigens, traffic to regional lymph nodes, and function in vivo as antigen-presenting cells to stimulate responses of CD4(+) T cells.